Analysis of HIV type 1 BF recombinant sequences from south america dates the origin of CRF12-BF to a recombination event in the 1970s - Dilernia, Darío Alberto (2011)
HIV-1 epidemics in South America are believed to have originated in part from the subtype B epidemic initiated in the Caribbean/North America region. However, circulation of BF recombinants in similar proportions was extensively reported. Information currently shows that many BF recombinants share a recombination structure similar to that found in the CRF12-BF. In the present study, analyzing a set of 405 HIV sequences, we identified the most likely origin of the BF epidemic in an early event of recombination. We found that the subtype B epidemics in South America analyzed in the present study were initiated by a founder event that occurred in the early 1970s, a few years after the introduction of these strains in the Americas. Regarding the F/BF recombinant epidemics, by analyzing a subtype F genomic segment within the viral gene gag present in the majority of the BF recombinants, we found evidence of a geographic divergence very soon after the introduction of subtype F strains in South America. Moreover, through analysis of a subtype B segment present in all the CRF12-BF-like recombination structure, we estimated the circulation of the subtype B strain that gave rise to that recombinant structure around the same time period estimated for the introduction of subtype F strains. The HIV epidemics in South America were initiated in part through a founder event driven by subtype B strains coming from the previously established epidemic in the north of the continent. A second introduction driven by subtype F strains is likely to have encountered the incipient subtype B epidemic that soon after their arrival recombined with them, originating the BF epidemic in the region. These results may explain why in South America the majority of F sequences are found as BF recombinants. © Copyright 2011, Mary Ann Liebert, Inc.